Host Delipidation Mediated by Bacterial Effectors. Issue 3 (March 2021) - Mei, Ligang; Qiu, Xiaofeng; Jiang, Chen; Yang, Aimin
Abstract : Protein lipidation, the covalent attachment of a lipid moiety to a target protein, plays a critical role in many cellular processes in eukaryotic cells. Bacterial pathogens secrete various effectors to subvert the host signaling pathway as a mechanism of microbial pathogenesis. An increasing number of effectors from diverse bacterial pathogens function as cysteine proteases to cause irreversible delipidation of host lipidated proteins. This in turn results in disruption of crucial lipidation-mediated host signal transduction, thereby enabling pathogen survival and replication. In this review, we discuss the role of the bacterial effectors in interactions with the host and highlight our knowledge of irreversible host delipidation, with a focus on the common concerted biochemical mechanisms of the bacterial effectors. Highlights: Bacteria have evolved diverse effector proteins that function as cysteine proteases to cause irreversible delipidation of host lipidated proteins, thereby resulting in disruption of the host's lipidated-protein-mediated-signaling landscape as a mechanism of microbial pathogenesis. Yersinia YopT releases Rho GTPases from the plasma membrane by cleaving S -prenylated cysteine residues at the C terminus, resulting in destruction of the actin cytoskeleton of host cells. Shigella IpaJ deconjugates the N -myristoylation modification from Golgi-associated Arf1 GTPase, thereby disrupting Golgi organization. Legionella RavZ irreversibly cleaves phosphatidylethanolamine (PE)-modified LC3 (LC3-PE) to inhibit autophagosome formation. The pathogen's effector-catalyzed host delipidation has a common concerted mechanism, with three key sequential steps – membrane targeting, substrate recognition, and proteolysis – to achieve their function.